2005
DOI: 10.1108/01443330510791243
|View full text |Cite
|
Sign up to set email alerts
|

Where does all the money go? An investigation of donation filtration

Abstract: In tro duc tionThere has been much so cial and le gal de bate over the def i ni tion of the word "charity." For some it is a path way to heaven, for oth ers, it plays a de ci sive role in anti-trust cases. Charles Dick ens wrote "Char ity be gins at home and jus tice be gins next door." Lord Macnaghten's take on the Pre am ble to the Stat ute of Eliz a beth (1601) 43 Eliz. 1, c.4 (UK), whilst con sid ered to have its lim i ta tions, is widely regarded as a use ful start ing point for a le gal def i ni tion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Charity has been attributed to giving that includes not only the blood donations but a wide range of products to help the underprivileged. Charity is comprised of four major activities; the development of welfare trust to reduce poverty, increasing and promoting education, promotion of religion, and promotion of such initiatives that are beneficial to society (Shaikh and McLarney, 2005). The public donations are helpful to support the needy people in an era where government funding has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Charity has been attributed to giving that includes not only the blood donations but a wide range of products to help the underprivileged. Charity is comprised of four major activities; the development of welfare trust to reduce poverty, increasing and promoting education, promotion of religion, and promotion of such initiatives that are beneficial to society (Shaikh and McLarney, 2005). The public donations are helpful to support the needy people in an era where government funding has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Continuation of charity programs is vital, shifting the physical charity programs to virtual platforms is now inevitable. According to Shaikh and McLarney (2005), charity compromised of four major activities; the development of welfare trust to reduce poverty, increasing and promoting education, promotion of religion, and promotion of such initiatives that are beneficial to society. In order to develop effective charity programs, it is for charity drive managers to know the preference of potential donors in the type of activities, content, and conduct.…”
Section: Public E-charity Program Preferencesmentioning
confidence: 99%
“…Charity originates etymologically from "caritas," which means love in Latin Lichtenberg (2009). The concept of charity connotes welfare, education, religion and other society-oriented initiatives (Shaikh and McLarney, 2005). Meanwhile, Meer et al (2017) found that charitable giving behavior was decreasing, as the Great Recession.…”
Section: Literature Reviewmentioning
confidence: 99%